Does preoperative enteral or parenteral nutrition reduce postoperative complications in Crohn's disease patients: a meta-analysis. Issue 9 (September 2018) - Brennan, Gregory T.; Ha, Iris; Hogan, Christopher; Nguyen, Emily; Jamal, M. M.; Bechtold, Matthew L.; Nguyen, Douglas L.
Abstract : Objectives: Crohn's disease (CD) patients frequently develop complications that require surgery for management. The high prevalence of malnutrition in CD patients presents a challenge because poor preoperative nutritional status has been shown to increase postoperative complications. In this study, we assessed whether preoperative enteral nutrition (EN) or total parenteral nutrition (TPN) decreases postoperative complications in CD patients. Materials and methods: A three-point systematic and comprehensive literature search was carried out on multiple databases followed by a meta-analysis with results presented as odds ratio (OR) using two models, the Mantel-Haenszel model and the DerSimonian and Laird model. The I 2 measure of inconsistency was utilized to assess heterogeneity. If statistically significant heterogeneity was identified, the results underwent a separate sensitivity analysis. Results: Five studies met inclusion criteria totaling 1111 CD patients. The rate of postoperative complications in the group receiving preoperative nutrition (EN or TPN) support was 20.0% compared with 61.3% in the group who had standard care without nutrition support [OR=0.26, 95% confidence interval (CI): 0.07–0.99, P <0.001]. Postoperative complications occurred in 15.0% of patients in the group who received preoperative TPN compared with 24.4% in the group who did not (OR=0.65, 95% CI: 0.23–1.88, P =0.43). P ostoperative complications occurred in 21.9% in the group who received preoperative EN compared with 73.2% in the group that did not received preoperative EN (OR=0.09, 95% CI: 0.06–0.13, P <0.001). Conclusion: Preoperative nutrition supplementation reduces postoperative complications in CD patients. In particular, EN in CD patients before undergoing surgery is superior to standard of care without nutrition support with a number needed to treat of 2. There is a trend toward TPN being superior to standard of care without nutrition support, but this trend did not reach statistical significance. Further studies are necessary to evaluate specific components in EN or TPN that may be most beneficial for CD patients requiring surgical intervention.